(untitled) (Research, Society and Development, 2020)
Snappers, as the Lutjanidae are known, are widely distributed across the Western Atlantic, especially species of the genus Lutjanus, the most abundant for this region. They represent important fishing resources, being quite caught by commercial fishing. To the coast of Brazil, Western South Atlantic, the most captured species are L. purpureus, L. analis, L. synagris, O. chrysurus e o L. vivanus. The latter is commonly caught together with snapper L. purpureus. The objective of the work was to gather data of the Mitochondrial Control Region for these five species in order to discuss aspects of the genetic structure of their populations and test its efficiency as a species-specific marker. We analyzed a region of 390 bp of 5 ’portion for 827 snappers, being 107 of the species L. analis, 240 of L. purpureus, 272 of L. synagris, 56 of L. vivanus and 152 of O. chrysurus. We observed different levels of genetic diversity for the five species, in addition to the intense sharing of haplotypes in each, suggesting extensive genetic connectivity to the coast of Brazil. We believe that the different patterns of variation observed are related to the evolutionary history of species, allied with the bioecological peculiarities of each, being a product of historical events. That is why, we believe that CR is quite suitable for detecting loss of diversity resulting from historical population bottlenecks, not suitable for the diagnosis of overfishing. Besides that, we proved its usefulness as a species-specific marker, representing a new Barcode possibility for Lutjanidae.